Advances in Modeling the Immune Microenvironment of Colorectal Cancer - Yoon, Paul Sukwoo; Del Piccolo, Nuala; Shirure, Venktesh S.; Peng, Yushuan; Kirane, Amanda; Canter, Robert J.; Fields, Ryan C.; George, Steven C.; Gholami, Sepideh (Frontiers in Immunology, 2021)
Colorectal cancer (CRC) is the third most common cancer and second leading cause of cancer death in the US. CRC frequently metastasizes to the liver and these patients have a particularly poor prognosis. The infiltration of immune cells into CRC tumors and liver metastases accurately predicts disease progression and patient survival. Despite the evident influence of immune cells in the CRC tumor microenvironment (TME), efforts to identify immunotherapies for CRC patients have been limited. Here, we argue that preclinical model systems that recapitulate key features of the tumor microenvironment—including tumor, stromal, and immune cells; the extracellular matrix; and the vasculature—are crucial for studies of immunity in the CRC TME and the utility of immunotherapies for CRC patients. We briefly review the discoveries, advantages, and disadvantages of current in vitro and in vivo model systems, including 2D cell culture models, 3D culture systems, murine models, and organ-on-a-chip technologies.